Circular RNA_PDHX Promotes the Proliferation and Invasion of Prostate Cancer by Sponging MiR-378a-3p - Mao, Yuanshen; Li, Wenfeng; Hua, Bao; Gu, Xin; Pan, Weixin; Chen, Qi; Xu, Bin; Lu, Chao; Wang, Zhong (Frontiers in Cell and Developmental Biology, 2021)
Accumulating evidence shows that, the dysregulation of circular RNAs (circRNAs) is implicated in the pathogenesis of prostate cancer (PCa). However, the underlying mechanisms by which hsa_circ_0003768 (circPDHX) contributes to PCa remain elusive. The differentially-expressed circRNAs between PCa and normal tissues were identified by Gene Expression Omnibus dataset. The association of circPDHX and miR-378a-3p expression with the clinicopathological parameters and prognosis in patients with PCa was analysed by fluorescence in situ hybridization and The Cancer Genome Atlas dataset. MTT and Transwell assays as well as a xenograft tumor model were used to assess the functional role of circPDHX in PCa cells. circPDHX-specific binding with miR-378a-3p was validated by bioinformatic analysis, luciferase gene reporter, and RNA immunoprecipitation assays. As a result, we found that, increased expression of circPDHX was associated with Gleason score (P = 0.001) and pathogenic T stage (P = 0.01), and acted as an independent prognostic factor of poor survival (P = 0.036) in patients with PCa. Knockdown of circPDHX inhibited cell proliferation and invasion in vitro and in vivo, but ectopic expression of circPDHX reversed these effects. Furthermore, circPDHX negatively regulated miR-378a-3p expression, but miR-378a-3p counteracted circPDHX-induced cell proliferation and IGF1R expression in PCa cells. In conclusion, our findings demonstrated that circPDHX facilitated the proliferation and invasion of PCa cells by downregulating miR-378a-3p.